Heteropyknotic filament in spermatids of Triatoma melanocephala and T. vitticeps (Hemiptera, Triatominae) - Chaboli Alevi, Kaio Cesar [UNESP]; Mendonca, Priscila Pasquetto [UNESP]; Pereira, Nathalia Paiva [UNESP]; Rosa, João Aristeu da [UNESP]; Vilela de Azeredo Oliveira, Maria Tercilia [UNESP] (Taylor & Francis Ltd, 2014)
The species Triatoma melanocephala and T. vitticeps are vectors of Chagas disease in Brazil. An analysis of the number of chromosomes has led to the proposal of the exclusion of both these species and T. tibiamaculata from the Brasiliensis subcomplex because of their similarities to the triatomines of North America. T. melanocephala has been found to have morphologic characteristics that are very similar to those of T. vitticeps, and these species have been considered synonymous. Thus, this paper analyzes the spermiogenesis of T. melanocephala and T. vitticeps in order to compare the two and to evaluate another possible relationship between the species. This study describes spermatogenesis and observes the morphology, cell size, and cytogenetic characteristics of triatomines. In all T. melanocephala cells, a slightly prominent peripheral heteropyknotic filament was observed. In T. vitticeps, an extensive peripheral heteropyknotic filament was observed in spermatids. This filament was observed in either the periphery or the middle of the cell. Thus, this paper describes the spermiogenesis stage of two cryptic species of triatomines and suggests that the central heteropyknotic filament can be used as a tool in the diagnosis of T. vitticeps as a vector of Chagas disease.
Keywords: Cytogenetic; Taxonomy; Triatominae; Brasiliensis subcomplex